INFLUENCE OF UNILATERAL SCIATIC NERVE LIGATION ON THE TUMOR-BEARING RATS WITH THE FEATURES OF SYSTEMIC REGULATION - O. I. Kit; G. V. Zhukova; A. I. Shikhlyarova; A. S. Goncharova; S. Yu. Tkachev; T. P. Protasova; E. A. Lukbanova; M. V. Mindar (Сибирский онкологический журнал)
The issue of factors that modify the tumor process stays relevant. The effect of unilateral sciatic nerve ligation on the growth of Guerin's transplantable carcinoma and the lifespan of white outbred rats of the same age, which differed in adaptation status and aging rates, was studied.Material and Methods. The motor activity (open field test), the character and tension of the general nonspecific adaptional reactions of the body (AR) according to Garkavi–Kvakina–Ukolova, the dynamics of tumor sizes and the lifespan of rats after Guerin’s carcinoma transplantation were evaluated.Results. The effect of unilateral sciatic nerve ligation differed from the unidirectional negative effects known in tumor-bearing animals after bilateral ligation of the sciatic nerve. In groups with unilateral ligation of the sciatic nerve and a false operation, more than 40 % of animals showed an increase in lifespan compared with the maximum lifespan in the control group. At the same time, in the most cases, the tumor growth rate was similar to the control indicators or exceeded them (more 25 % of cases). A temporary inhibition of tumor growth was observed only in individual animals. There was no direct relationship between tumor growth or lifespan and the degree of decrease in the motor activity of animals 4 weeks after nerve ligation. A correlation between the changes in the ARs and lifespans of animals and, to a lesser extent, the dynamics of tumor growth was observed. The distinct negative effect of increased aging rate, measured by animal weight, on tumor development and lifespan in studied rats was shown, but not in the cases of sciatic nerve ligation. Unilateral sciatic nerve ligation had a multidirectional effect on tumor growth and lifespan in rats with different rates of aging, depending, probably, on the individual pain sensitivity and the individual features of systemic regulation of tumor-bearing animals.Conclusion. The results reflect the complex relationship between processes associated with chronic pain, oncogenesis, aging and features of neuroendocrine and immune regulation of experimental animals. The question of the reasons for the preservation of viability in animals that underwent surgery and ligation of the sciatic nerve, when the tumors reach large sizes, exceeding this indicator in the control group, needs to be clarified.